TECHNOLOGY OF CULTIVATION OF PEKING CABBAGE IN VARIOUS SCHEMES - Khurramov Ulugbek Holmamatovich; SharipovaShoxsanamShuxrat daughter; Maxsidaliyeva Tuxtaniso Oxunjon daughter (Scholar Express Journals, 2021)
In the Republic, cultivation of Peking cabbage has not enough scientificallybased recommendations on nutrition and placement methods, so many scientists and practitioners have been experimenting with the most delicate habitats in cultivating Peking cabbage and achieving high productivity. In our research, we obtained a 70×30 cm planting scheme as a comparative option."Xibinskaya" sort of the Peking cabbage was identified on the basis of crop yields and economic efficiency of 2016-2021, which was cultivated on 7 different schemes, as a replica. The article describes the results of experiments on determining the best nutrition of Peking cabbage
Keywords: Peking cabbage; sort; hybrid; yield